Comparison of three processes for phosphorus recovery from wastewater sludge using process modelling - Kotze, Andrea (Stellenbosch : Stellenbosch University, 2025)
Kotze, A. 2025. Comparison of three processes for phosphorus recovery from wastewater sludge using process modelling. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/c00923e7-51a2-49ef-90e6-328600fea7f3